Are Individuals Bayesian Decision Makers - Viscusi, W. Kip (American Economic Review, 1985)
There has been increasing interest in whether normative models of individual choice under uncertainty accord with actual behavior. These concerns have been much greater than in other economic contexts because of the particularly severe demands such decisions place on the rationality of the decision maker. The limitations of these decisions have widespread consequences, as they provide the rationale for many governmental efforts to regulate the risks people face. Here I explore the issues raised by a Bayesian decision framework, focusing particularly on my analyses of worker and consumer behavior.